A kind of quick-hardening cement mortar and application method thereof

By using galvanized steel fibers and polymer fibers in cement mortar, the compressive stress generated by cement hydration heat is solved, and the problem of cement block cracking due to violent expansion and contraction is achieved.

CN119661168BActive Publication Date: 2025-04-29GRANDBLUE ENVIRONMENT CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510201530.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-29
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problem of cement block cracking caused by expansion and contraction caused by intense hydration of cement.

Method used

By using galvanized steel fibers and polymer fibers in cement mortar, polymer fibers use the environment of severe hydration and heat in a short time to generate compressive stress, and work in concert with galvanized steel fibers to enhance the anti-dry cracking performance of the cement block.

Benefits of technology

The overall anti-cracking effect of cement blocks is achieved, the cracking phenomenon of cement blocks is reduced, and the amount of fiber is reduced by controlling the average preload coefficient of polymer fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_26
    Figure SMS_26
  • Figure SMS_27
    Figure SMS_27
  • Figure SMS_28
    Figure SMS_28
Patent Text Reader

Abstract

The present application discloses a fast-hardening cement mortar and an application method thereof, and relates to the technical field of building materials. The fast-hardening cement mortar is composed of the following components: fast-hardening sulphoaluminate cement, ordinary Portland cement, aggregate, admixture and fiber composition; the fiber composition includes galvanized steel fiber and polymer fiber, and the polymer fiber includes PVA fiber; the surface of the galvanized steel fiber and the polymer fiber is formed with a film layer modified by a silane coupling agent, and the silane coupling agent is selected from at least one of aminopropyltriethoxysilane and diamino-type functional group silane. The present application adopts galvanized steel fiber and polymer fiber in cement mortar. The polymer fiber utilizes the environment of intense hydration heat of cement in a short period of time to generate compressive stress in the cement block, and produces a synergistic effect with the galvanized steel fiber to produce an overall anti-cracking effect of the cement block; through the surface modification scheme of the silane coupling agent, its anti-cracking effect is enhanced, so that it can achieve the effect of ordinary long fibers with short fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building materials, and in particular to a rapid-hardening cement mortar and an application method thereof. Background Art

[0002] At present, municipal facilities such as roads and sewage wells often need to be repaired at damaged locations. In order to reduce the enclosure time after construction and open to traffic as soon as possible, ultra-early-strength and fast-hardening cement-based repair materials are often used. This type of material usually has a compressive strength of more than 20MPa 2 to 3 hours after adding water, and has a solidification time of more than 20 minutes and good fluidity, which is convenient for pouring and troweling.

[0003] However, due to the fast-hardening and early-strengthening properties of this type of material, a violent cement hydration reaction will occur within tens of minutes after construction, and a large amount of hydration heat will be generated, which will cause the volume of the completed cement block to expand. After most of the reactions are completed, the total volume of the newly formed dense solid phase is smaller than that of the unhardened cement mortar, so the cement block will shrink. At the same time, as the hydration heat is released, cooling will also cause the hardened cement block to shrink in volume. The combined shrinkage effects of the two cause the hardened cement block to crack, and this cracking phenomenon is more serious in cement materials with a shorter curing time.

[0004] The solution in the related art is to add auxiliary materials such as fly ash and sand to cement to replace part of the cement powder and reduce the overall hydration heat release. The disadvantage of this solution is that the addition of various powders and aggregates will have an adverse effect on the compressive strength of the cement slurry after solidification. For early-strengthening and fast-hardening cement-based materials, the amount of participation should not be too much, otherwise the 2-hour strength will not meet the standard.

[0005] Another common solution is to add a certain amount of expansion agent to the formula to offset the shrinkage effect of cement curing. Common expansion agents include magnesium oxide expansion agent, calcium sulfoaluminate, etc. (such as the patent with publication number CN117819921A). However, this type of admixture may produce a composite effect with other complex admixtures, cannot effectively solve the anti-cracking problem, and increases production costs and difficulty. Summary of the invention

[0006] The purpose of the present application is to provide a fast-hardening cement mortar to solve the problem of cracking of cement blocks caused by the cement first expanding after intense hydration heat and then shrinking during solidification.

[0007] The present invention provides a rapid-hardening cement mortar, which is composed of the following components in parts by mass:

[0008] 60-90 parts of rapid hardening sulphoaluminate cement, 10-40 parts of ordinary Portland cement, 80-120 parts of aggregate, 0.5-3 parts of admixture and 0.5-4 parts of fiber composition; the fiber composition comprises galvanized steel fiber and polymer fiber, and the polymer fiber comprises PVA fiber;

[0009] Wherein, a film layer modified by a silane coupling agent is formed on the surface of the galvanized steel fiber and the polymer fiber, and the silane coupling agent is selected from at least one of aminopropyltriethoxysilane and diamino-type functional group silane.

[0010] Preferably, the surface film layer of the galvanized steel fiber and the polymer fiber is a composite film layer modified by aminopropyltriethoxysilane and bisamino-type functional group silane; and / or, the modification process of the galvanized steel fiber and the polymer fiber is firstly impregnated with bisamino-type functional group silane and then dried, and then impregnated with aminopropyltriethoxysilane and then dried.

[0011] Preferably, the average preload coefficient of the polymer fiber is The range is 3000Pa / ℃~6000Pa / ℃, the average preload coefficient The calculation method is:

[0012] ;in, For the The mass fraction corresponding to each polymer fiber; For the The elastic modulus corresponding to each polymer fiber; For the The thermal expansion coefficient corresponding to each polymer fiber; n is the number of types of polymer fibers; is the loop variable, =1, 2, ..., n;

[0013] And / or, the polymer fiber further includes at least one of PP fiber, PAN fiber, PET fiber or PA6 fiber.

[0014] Preferably, the length ratio of the galvanized steel fiber and the polymer fiber is (2~4):1; and / or the fiber length of the galvanized steel fiber is 12mm~18mm, and the length of the polymer fiber is 3mm~8mm; and / or the length of the galvanized steel fiber is 15mm, and the length of the polymer fiber is 5mm.

[0015] Preferably, the mass ratio of the fiber composition to the total amount of rapid-hardening sulphoaluminate cement and ordinary Portland cement is (2-4):100; and / or, the mass ratio of the galvanized steel fiber to the polymer fiber is (1-3):(0.5-1.5).

[0016] Preferably, the thickness of the zinc layer in the galvanized steel fiber is 0.2 μm to 0.6 μm.

[0017] Preferably, the rapid-hardening cement mortar is composed of the following components in parts by mass: 70-80 parts of rapid-hardening sulphoaluminate cement, 20-30 parts of ordinary Portland cement, 90-110 parts of aggregate, 1-3 parts of galvanized steel fiber, 0.5-2 parts of PVA fiber, and 1-2 parts of admixture.

[0018] Preferably, the rapid-hardening cement mortar is composed of the following components in parts by mass: 75 parts of rapid-hardening sulphoaluminate cement, 25 parts of ordinary Portland cement, 100 parts of aggregate, 2 parts of copper-coated steel fiber, 1 part of PVA fiber and 1.39 parts of admixture.

[0019] The invention also provides an application method of the rapid-hardening cement mortar, which comprises weighing the rapid-hardening cement mortar according to a mass fraction ratio, adding water, stirring and mixing the mortar uniformly.

[0020] Preferably, when using 180-220 parts by mass of the rapid-hardening cement mortar, 20-30 parts of water are added during stirring.

[0021] Compared with the prior art, the beneficial effects of this application are:

[0022] The present application adopts galvanized steel fibers and polymer fibers in cement mortar. The polymer fibers utilize the intense hydration heat environment of cement in a short period of time to generate compressive stress in the cement block, and at the same time produce a synergistic effect with the galvanized steel fibers to produce an overall anti-cracking effect for the cement block.

[0023] Secondly, through the surface modification scheme of silane coupling agent, its anti-cracking effect is enhanced, so that it can achieve the effect of ordinary long fibers with short fibers; at the same time, the short fiber method ensures the convenience of the construction mixing process and the uniformity of the dispersion of the fiber composition in the cement mortar.

[0024] Furthermore, the present invention controls the average preload coefficient of the polymer fibers in the cement block, thereby better utilizing the hydration heat released by the cement to cause the elongation and deformation of the polymer fibers, and better utilizing the local stress generated during the cooling process; further, by controlling the average preload coefficient of the polymer fibers in the cement block, the amount of polymer fibers used can be greatly reduced. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] The invention provides a fast-hardening cement mortar, which is composed of the following components in parts by mass: 60-90 parts of fast-hardening sulphoaluminate cement, 10-40 parts of ordinary Portland cement, 80-120 parts of aggregate, 0.5-3 parts of admixture and 0.5-4 parts of fiber composition; the fiber composition comprises galvanized steel fiber and polymer fiber, and the polymer fiber comprises PVA fiber; wherein a film layer modified by a silane coupling agent is formed on the surface of the galvanized steel fiber and the polymer fiber, and the silane coupling agent is selected from at least one of aminopropyltriethoxysilane and diamino-type functional group silane.

[0027] First, by evenly distributing galvanized steel fibers and polymer fibers in the cement body, once cracks occur, they need to overcome the bonding force between the fibers and the cement block to continue to expand. In view of the surface characteristics of the galvanized layer of steel fibers and the surface characteristics of PVA fibers, the fiber combination scheme formed by the modification of the above-mentioned compound silane coupling agent can play a further positive role in crack resistance, and can further effectively transmit external mechanical impacts and reduce local cracking caused by stress concentration. Secondly, PVA fibers play a major role in resisting cement shrinkage cracking in the early stage. Galvanized steel fibers are expensive and do not help much in the early 2-hour compressive strength; however, the use of galvanized steel fibers can increase the service life and resist the rolling and impact of vehicles during use. Its life advantage is significantly higher than that of polymer fibers. Furthermore, the use of galvanized steel fibers, rather than other metal coatings (such as copper), can better cope with the corrosive environment of sewage with complex chemical components around sewage wells.

[0028] In this way, the present application adopts galvanized steel fibers and polymer fibers in cement mortar. The polymer fibers utilize the intense hydration heat environment of cement in a short period of time to generate compressive stress in the cement block, and at the same time produce a synergistic effect with the galvanized steel fibers to produce an overall anti-cracking effect for the cement block.

[0029] The present invention has no particular limitation on rapid hardening sulphoaluminate cement and ordinary Portland cement, and those skilled in the art may be used; for example, the compressive grade of the rapid hardening sulphoaluminate cement R.SAC used may be 42.5, and the compressive grade of the ordinary Portland cement PO used may be 52.5.

[0030] In one embodiment of the present invention, the surface film layer of the galvanized steel fiber and the polymer fiber is a composite film layer modified by aminopropyltriethoxysilane and bisamino-type functional group silane; and / or, the modification process of the galvanized steel fiber and the polymer fiber is first impregnated with bisamino-type functional group silane and then dried, and then impregnated with aminopropyltriethoxysilane and then dried.

[0031] Through a variety of silane coupling agent modification research schemes, the zinc-plated surface and PVA surface in the fiber composition were modified with aminopropyltriethoxysilane and diamino-functional silane, and the final cement block formed had better anti-cracking effect. It is preliminarily speculated that the silane coupling agent modification scheme adopted can significantly increase the -OH groups attached to the fiber surface, and then the -OH groups on the fiber surface can form strong hydrogen bonds with the -OH groups in the cement paste, greatly improving the bonding strength of the two fibers and the cement paste after curing. In addition, the above-mentioned composite surface modification can significantly reduce the amount of fiber used to achieve the design index.

[0032] In one embodiment of the present invention, the average preload coefficient of the polymer fiber is The range is 3000Pa / ℃~6000Pa / ℃; and / or, the polymer fiber also includes at least one of PP fiber, PAN fiber, PET fiber or PA6 fiber.

[0033] Average preload coefficient In the polymer fiber solution with a range of 3000Pa / ℃~6000Pa / ℃, the formed high molecular compound stretches freely after being heated and is locked in the elongated state by cement solidification, which is very suitable for ultra-early strength cement-based materials with intense hydration heat generated in a short period of time. Furthermore, the above-mentioned polymer fiber first stretches a certain amount at high temperature and is locked and combined with the cement block. Then, when cooled to a low temperature, the polymer fiber will shrink, and the cement block will prevent the fiber from shrinking, thereby generating a preload, and finally preventing the generation of cracks or the spread of cracks.

[0034] In the process of developing polymer fibers based on the need to prevent block crack propagation, it was found that the polymer fiber solution focuses on its elastic modulus E and thermal expansion coefficient α. The elastic modulus E of polymer fibers ranges from 9GPa to 40GPa, and the thermal expansion coefficient α ranges from 30×10 -6 / ℃~200×10 -6 / ℃. It is preliminarily speculated that a single polymer fiber generates a local compressive stress F on the cement block, and the deduction process of the local compressive stress F is as follows:

[0035] ;

[0036] Where, E is the elastic modulus; s is the fiber cross-sectional area; ΔL is the fiber elongation length; L is the original fiber length; is the thermal expansion coefficient; ΔT is the temperature difference.

[0037] Average preload coefficient of polymer fibers for various polymer fiber combinations The calculation method is:

[0038] ;

[0039] in, For the The mass fraction corresponding to each polymer fiber; For the The elastic modulus corresponding to each polymer fiber; For the The thermal expansion coefficient corresponding to each polymer fiber; n is the number of types of polymer fibers; is the loop variable, =1, 2, ..., n.

[0040] In addition, since the linear thermal expansion coefficient of the cement block itself is 10×10 -6 / ℃, when the α value of the polymer fiber used is lower than this value, its anti-cracking effect will be affected.

[0041] In one embodiment of the present invention, the length ratio of the galvanized steel fiber and the polymer fiber is (2~4):1; and / or the fiber length of the galvanized steel fiber is 12~18mm, and the length of the polymer fiber is 3~8mm; and / or the length of the galvanized steel fiber is 15mm, and the length of the polymer fiber is 5mm.

[0042] First, galvanized steel fiber and polymer fiber adopt short fiber scheme, and the upper limit of their length is 18mm and 8mm respectively, mainly considering that overlong fiber affects the uniform dispersion effect in actual construction. The length of galvanized steel fiber can be selected from 12mm, 14mm, 15mm, 16mm and 18mm. When the length of galvanized steel fiber is controlled to 15mm, it can meet the uniformity of the mixing process and the design requirements of the flexural strength and compressive strength of the cement block at the same time; moreover, although overlong steel fiber can improve the flexural strength to a certain extent, the improvement effect on compressive strength is very limited. The length ratio of galvanized steel fiber and polymer fiber can be 2:1, 3:1 or 4:1, mainly considering that when the length of polymer fiber is too long, it is easy to entangle with galvanized steel fiber, and the agglomeration of the two will affect the deformation of polymer fiber and its stress conduction effect. The study found that when the length of galvanized steel fiber is 15mm and the length of polymer fiber is 5mm, the combination of the two has a significant and superior effect on preventing the expansion of cement block cracks.

[0043] At the same time, through the surface modification scheme of silane coupling agent, its anti-cracking effect is enhanced, so that it can achieve the effect of ordinary long fibers with short fibers; at the same time, the short fiber method ensures the convenience of the construction mixing process and the uniformity of the dispersion of the fiber composition in the cement mortar.

[0044] In one embodiment of the present invention, the mass ratio of the fiber composition to the total amount of rapid-hardening sulphoaluminate cement and ordinary Portland cement is (2-4):100; and / or, the mass ratio of galvanized steel fiber to polymer fiber is (1-3):(0.5-1.5).

[0045] If the mass fraction ratio of the fiber composition to the total amount of rapid hardening sulphoaluminate cement and ordinary Portland cement is too high, the compressive strength of the formed cement block will be affected. The ratio of the two can be controlled at 2:100, 2.5:100, 3:100, 3.5:100. Preferably, when the ratio of the two is controlled at 3:100, the bonding force between the fiber and cement can be greatly enhanced to ensure the compressive and flexural strength.

[0046] The mass ratio of the galvanized steel fiber to the polymer fiber can be 1:1, 2:1, 3:1, 1:0.5, 1:1.5. Preferably, the ratio is controlled to be 2:1.

[0047] In one embodiment of the present invention, the thickness of the zinc layer in the galvanized steel fiber is 0.2-0.6 μm. The thickness of the zinc layer can be selected from 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm and 0.6 μm; the thicker the zinc layer, the stronger the corrosion resistance of the steel fiber; however, the zinc layer will cause a significant increase in cost and affect the compressive strength and flexural strength of the formed cement block. Among them, the zinc layer thickness of 0.5 μm can better balance the anti-cracking and service life effects. According to the calculation of 50 nanometers of corrosion per year, the cement block is expected to be usable for 10 years after its formation.

[0048] In one embodiment of the present invention, the fast-hardening cement mortar is composed of the following components in parts by mass: 70-80 parts of fast-hardening sulphoaluminate cement, 20-30 parts of ordinary Portland cement, 90-110 parts of aggregate, 1-3 parts of galvanized steel fiber, 0.5-2 parts of PVA fiber, and 1-2 parts of admixture.

[0049] In one embodiment of the present invention, the rapid-hardening cement mortar is composed of the following components in parts by mass: 75 parts of rapid-hardening sulphoaluminate cement, 25 parts of ordinary Portland cement, 100 parts of aggregate, 2 parts of copper-coated steel fiber, 1 part of PVA fiber and 1.39 parts of admixture.

[0050] The invention also provides an application method of the rapid-hardening cement mortar, which comprises weighing the rapid-hardening cement mortar according to the mass fraction ratio, adding water and stirring and mixing the mortar uniformly.

[0051] In one embodiment of the present invention, when using 180-220 parts by mass of rapid-hardening cement mortar, 20-30 parts of water are added during stirring.

[0052] In one embodiment of the present invention, when using fast-hardening cement mortar, the fast-hardening cement mortar contains 75 parts of fast-hardening sulphoaluminate cement, 25 parts of ordinary Portland cement and 100 parts of aggregate; when using 220 parts of fast-hardening cement mortar by mass, 30 parts of water are added during stirring.

[0053] In order to further illustrate the present invention, a rapid-hardening cement mortar and an application method thereof provided by the present invention are described in detail below in conjunction with embodiments.

[0054] Embodiment 1

[0055] The embodiment of the present application discloses a fast-hardening cement mortar, which is composed of the following components in parts by weight: 75 parts of fast-hardening sulphoaluminate cement, 25 parts of ordinary Portland cement, 100 parts of aggregate, 1.39 parts of admixture, 2 parts of galvanized steel fiber and 1 part of PVA fiber.

[0056] The aggregate is ordinary river sand or machine-made sand for construction. The admixtures include 0.5 parts of polycarboxylic acid water reducer, 0.44 parts of tartaric acid retarder, 0.4 parts of early strength agent, and 0.05 parts of defoamer. The selected galvanized steel fiber has a length of 15 mm, a diameter of 0.2 mm, and a zinc coating thickness of 0.5 μm; the PVA fiber has a length of 5 mm and a diameter of 25 μm.

[0057] This embodiment sets up multiple treatment groups and control groups, and designs different fiber composition modification schemes. Among them, the fiber composition modification process: the fiber composition is immersed in a silane coupling agent and then dried to form a corresponding film, and then immersed in another silane coupling agent according to specific needs and then dried. The specific operation of the application process of cement mortar: according to the fiber composition design scheme in the above table below, weigh the fast-hardening cement mortar of the above components, add 30 parts of water, stir evenly to form a corresponding cement block, place and cure for 2 hours, test its 2-hour compressive strength and 2-hour flexural strength, and the relative value K of cement shrinkage reduction after 4 hours.

[0058] The evaluation method for reducing the shrinkage of cement blocks is as follows: a blank group is set up, and the components of the cement mortar are 75 parts of rapid hardening sulphoaluminate cement, 25 parts of ordinary Portland cement, 100 parts of aggregate, and 1.39 parts of admixture, without adding any fiber composition; after the above composition is mixed evenly, 30 parts of water are added, and the corresponding cement blocks are formed after stirring evenly. The length shrinkage of the cement blocks in the blank group after molding and 4 hours is measured as L0. For different treatment groups and comparison groups, the length shrinkage of the cement blocks after molding and 4 hours is measured as L i , and calculate the relative value of shrinkage reduction K = (L0-L i ) / L0.

[0059] The specific results of the treatment group, comparison group and blank group in this example are shown in Table 1 below.

[0060] Table 1 Test results of different modification schemes and their corresponding cement blocks

[0061]

[0062] It can be found that compared with the control group A1, the overall compressive strength, flexural strength and relative shrinkage reduction of the treatment groups A1~A3 after modification with silane coupling agent are better; moreover, the anti-shrinkage effect of the fiber composition is greatly improved after it has been modified with two silane coupling agents.

[0063] Embodiment 2

[0064] The embodiment of the present application discloses a fast-hardening cement mortar, which is composed of the following components in parts by mass: 75 parts of fast-hardening sulphoaluminate cement, 25 parts of ordinary Portland cement, 100 parts of aggregate, 1.39 parts of admixture, 2 parts of galvanized steel fiber and 1 part of polymer fiber in total, and the galvanized steel fiber and the polymer fiber are successively impregnated with coupling agent aminopropyltriethoxysilane and diamino functional group silane and then dried.

[0065] The admixtures include 0.5 parts of polycarboxylic acid water reducer, 0.44 parts of tartaric acid retarder, 0.4 parts of early strength agent, and 0.05 parts of defoamer. The length of the galvanized steel fiber is 15 mm, the diameter is 0.2 mm, and the thickness of the zinc coating is 0.5 μm.

[0066] This embodiment sets up multiple treatment groups and comparison groups, designs different fiber composition matching schemes, and calculates the average preload coefficient of the polymer fiber. The specific operation of the cement mortar application process is as follows: according to the fiber composition design scheme in the table below, weigh the quick-hardening cement mortar of the above components, add 30 parts of water, stir evenly to form a corresponding cement block, place and cure for 2 hours, test its 2-hour compressive strength and 2-hour flexural strength, and the relative value K of cement shrinkage reduction after 4 hours. The test method of the relative value K of shrinkage reduction can be found in Example 1.

[0067] The specific results of the treatment group, comparison group and blank group in this example are shown in Table 2 below.

[0068] Table 2 Test results of different modification schemes and their corresponding cement blocks

[0069]

[0070] It can be found that from the perspective of anti-shrinkage effect, the solution using single PVA fiber in treatment group B1 has the best performance; using PVA fiber and PAN fiber, as well as PVA fiber and PET fiber can also achieve a certain anti-shrinkage effect.

[0071] In this way, the present invention controls the average preload coefficient of the polymer fibers in the cement block, thereby better utilizing the hydration heat released by the cement to cause the elongation and deformation of the polymer fibers, and better utilizing the local stress generated during the cooling process; further, by controlling the average preload coefficient of the polymer fibers in the cement block, the amount of polymer fibers used can be greatly reduced.

[0072] Embodiment 3

[0073] The embodiment of the present application discloses a fast-hardening cement mortar, which is composed of the following components in parts by mass: 75 parts of fast-hardening sulphoaluminate cement, 25 parts of ordinary Portland cement, 100 parts of aggregate, 1.39 parts of admixture, and several parts of fiber composition, and galvanized steel fiber and polymer fiber are successively impregnated with coupling agent aminopropyltriethoxysilane and diamino functional group silane and then dried.

[0074] The admixtures include 0.5 parts of polycarboxylate water reducer, 0.44 parts of tartaric acid retarder, 0.4 parts of early strength agent, and 0.05 parts of defoamer. The fiber composition is composed of galvanized steel fiber and polymer fiber. The galvanized steel fiber has a length of 15 mm, a diameter of 0.2 mm, and a zinc coating thickness of 0.5 μm; the PVA fiber has a length of 5 mm and a diameter of 25 μm.

[0075] This embodiment sets up multiple treatment groups and control groups, and adjusts the addition amount of galvanized steel fiber and PVA fiber and the water consumption of fast-hardening cement mortar. Specific operation of cement mortar application process: according to the design scheme in the above table, weigh the fast-hardening cement mortar of the above components, add a certain amount of water, stir evenly to form a corresponding cement block, place and cure for 2 hours, test its 2-hour compressive strength and 2-hour flexural strength, and the relative value K of shrinkage reduction of cement after 4 hours. The test method of the relative value K of shrinkage reduction can be found in Example 1.

[0076] The specific results of the treatment group, comparison group and blank group in this example are shown in Table 3 below.

[0077] Table 3 Test results of different modification schemes and their corresponding cement blocks

[0078]

[0079] It is found that treatment groups C1~C4 only use galvanized steel fibers. As the amount of galvanized steel fibers added increases, during the use of cement mortar, the amount of water used is forced to increase to maintain the fluidity of the entire mortar. Otherwise, the material affects the filling density and the setting time is shortened, affecting the construction. The reason is that the fiber itself will increase the viscosity of the slurry, and the fiber surface will adsorb a certain amount of water, thereby deteriorating the fluidity of the material. Compared with the control group C1, treatment groups C1~C4 only increase the amount of galvanized steel fibers, and the compression and flexural properties cannot be significantly improved. On the contrary, the forced increase in water consumption will deteriorate. Under the premise of maintaining a certain range of fluidity, increasing the amount of water will significantly deteriorate the compression and flexural properties while improving the flow. Moreover, in the early strength system, the amount of water has an important influence on various indicators. Therefore, the optimization scheme is to use as little water as possible while maintaining a certain fluidity.

[0080] Secondly, comparing treatment groups C1-C4 and C5-C8, the addition of PVA fiber alone significantly improved the compressive strength, flexural strength and cement shrinkage reduction compared to the addition of galvanized steel fiber alone. Moreover, as the amount of PVA fiber added increased, the fluidity of the slurry also decreased, and the improvement of compressive and flexural strength was relatively general.

[0081] Furthermore, compared with treatment groups C1-C4 and treatment groups C5-C8, treatment groups C9-C11 used a composite solution of galvanized steel fiber and PVA fiber, and the overall compressive strength, flexural strength and the degree of reduction of cement shrinkage were the most obvious. Moreover, by reasonably controlling the ratio of galvanized steel fiber and PVA fiber and the comprehensive water consumption, the solution of treatment group C10 was the best, and the ratio of its fiber composition dosage to the sum of rapid hardening sulphoaluminate cement and ordinary Portland cement was only 3:100. The extremely low dosage of fiber composition can ensure the compressive, flexural and anti-bearing effects, and the compressive strength of the cement block formed by treatment group C10 is ≥20MPa.

[0082] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A rapid-hardening cement mortar, characterized in that: The rapid hardening cement mortar is composed of the following components in parts by mass: 60-90 parts of rapid hardening sulphoaluminate cement, 10-40 parts of ordinary Portland cement, 80-120 parts of aggregate, 0.5-3 parts of admixture and 0.5-4 parts of fiber composition; the fiber composition comprises galvanized steel fiber and polymer fiber, and the polymer fiber comprises PVA fiber; Wherein, the average preload coefficient of the polymer fiber is The range is 3000Pa / ℃~6000Pa / ℃, the average preload coefficient The calculation method is: ;in, For the The mass fraction corresponding to each polymer fiber; For the The elastic modulus corresponding to each polymer fiber; For the The thermal expansion coefficient corresponding to each polymer fiber; n is the number of types of polymer fibers; is the loop variable, =1, 2, ..., n; A film layer modified by a silane coupling agent is formed on the surface of the galvanized steel fiber and the polymer fiber; the surface film layer of the galvanized steel fiber and the polymer fiber is a composite film layer modified by aminopropyltriethoxysilane and bisamino-type functional group silane; and / or, the modification process of the galvanized steel fiber and the polymer fiber is first impregnated with bisamino-type functional group silane and then dried, and then impregnated with aminopropyltriethoxysilane and then dried.

2. A rapid hardening cement mortar according to claim 1, characterized in that: The polymer fiber also includes at least one of PP fiber, PAN fiber, PET fiber or PA6 fiber.

3. A rapid hardening cement mortar according to claim 1, characterized in that: The length ratio of the galvanized steel fiber and the polymer fiber is (2~4):1; and / or the fiber length of the galvanized steel fiber is 12mm~18mm, and the length of the polymer fiber is 3mm~8mm.

4. A rapid hardening cement mortar according to claim 3, characterized in that: The length of the galvanized steel fiber is 15 mm, and the length of the polymer fiber is 5 mm.

5. The rapid hardening cement mortar according to claim 1, characterized in that: The mass ratio of the fiber composition to the total amount of rapid-hardening sulphoaluminate cement and ordinary Portland cement is (2-4):100; and / or the mass ratio of the galvanized steel fiber to the polymer fiber is (1-3):(0.5-1.5).

6. The rapid hardening cement mortar according to claim 1, characterized in that: The thickness of the zinc layer in the galvanized steel fiber is 0.2 μm to 0.6 μm.

7. A rapid hardening cement mortar according to any one of claims 1 to 6, characterized in that: The rapid-hardening cement mortar is composed of the following components in parts by mass: 70-80 parts of rapid-hardening sulphoaluminate cement, 20-30 parts of ordinary Portland cement, 90-110 parts of aggregate, 1-3 parts of galvanized steel fiber, 0.5-2 parts of PVA fiber, and 1-2 parts of admixture.

8. The rapid hardening cement mortar according to claim 7, characterized in that: The rapid-hardening cement mortar is composed of the following components in parts by mass: 75 parts of rapid-hardening sulphoaluminate cement, 25 parts of ordinary Portland cement, 100 parts of aggregate, 2 parts of galvanized steel fiber, 1 part of PVA fiber and 1.39 parts of admixture.

9. The application method of the rapid-hardening cement mortar according to any one of claims 1 to 8, characterized in that: The rapid-hardening cement mortar is weighed according to the mass ratio, and water is added to stir and mix evenly.

10. The application method of the rapid-hardening cement mortar according to claim 9, characterized in that: When using 180-220 parts by mass of the rapid-hardening cement mortar, 20-30 parts of water are added during stirring.

Citation Information

Patent Citations

  • Composition for polymer mortar, polymer mortar as well as preparation method and application of polymer mortar

    CN117819921A

  • Quick-setting cement mortar and preparation method for quick-setting cement mortar

    CN102584149A

  • Quick-setting and quick-hardening early-strength and high-strength pavement patching material and preparation method thereof

    CN114349440A